Does labor diversity affect firm productivity? - Pierpaolo Parrotta; Dario Pozzoli; Mariola Pytlikova (Institute for the Study of Labor (IZA), 2012)
Using a matched employer-employee data-set, we analyze how workforce diversity in terms of cultural background, education and demographic characteristics affects the productivity of firms in Denmark. Implementing a structural estimation of the firms' production function (Ackerberg et al. 2006), we find that labor diversity in education significantly enhances a firm's value added. Conversely, diversity in ethnicity and demographics induces negative effects on firm productivity. Therefore, the negative effects, which are derived from the communication and integration costs associated with a more culturally and demographically diverse workforce, seem to outweigh the positive effects of creativity and knowledge spillovers.
Keywords: J15; J16; J24; J61; J81; L20; 330; labor diversity; skill complementarity; communication barriers; total factor productivity; Humankapital; Diversity Management; Kommunikation; Produktivität; Dänemark